1986
DOI: 10.1007/bf00053807
|View full text |Cite
|
Sign up to set email alerts
|

Study of metal aerosol systems as a sink for atmospheric SO2

Abstract: The chemical removal of SO 2 in the presence of different aerosol systems has been investigated in laboratory experiments using a dynamic flow reactor. The aerosols consisted of wetted particles containing one of the following substances: MnC12, Mn(NO3)2, MnSO4, CuCI2, Cu(NO3)2, CuSO4, FeC13, NaCI. The SO2 removal rate R was measured as a function of the SO2 gas phase concentration (SO 2)g, the spatial metal concentration CMe , and the relative humidity rH in the reactor. A first-order dependence with regard t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…Allen et al, 2002]. The potential mech anism is as yet unclear, but it has been suggested that nucle ation on ultrafine metal chlorides may play a role, with the metallic cations enhancing the reaction rate [Berresheim and Jaeschke, 1986]. Once formed, this sulfuric acid may modify trace metal speciation by revolatilisation of HC1 and the for mation of metal sulfates: 2XC1 (s) + H 2 S0 4 (1) <=> X 2 S0 4 (s/aq) + 2HC1 (g) Etna volcano frequently shows distinctive differences between the emissions from lava flows, degassed at low pressures, and the summit plumes [e.g.…”
Section: High-temperature Gas Phase Reaction Productsmentioning
confidence: 98%
“…Allen et al, 2002]. The potential mech anism is as yet unclear, but it has been suggested that nucle ation on ultrafine metal chlorides may play a role, with the metallic cations enhancing the reaction rate [Berresheim and Jaeschke, 1986]. Once formed, this sulfuric acid may modify trace metal speciation by revolatilisation of HC1 and the for mation of metal sulfates: 2XC1 (s) + H 2 S0 4 (1) <=> X 2 S0 4 (s/aq) + 2HC1 (g) Etna volcano frequently shows distinctive differences between the emissions from lava flows, degassed at low pressures, and the summit plumes [e.g.…”
Section: High-temperature Gas Phase Reaction Productsmentioning
confidence: 98%
“…Heterogeneous oxidation (on the surface of aerosol particles and in cloud and fog droplets) is dominated by reactions with either dissolved ozone, hydrogen peroxide, or molecular oxygen, the latter pathway being catalyzed by transition metal ions (Harris et al, 2013;Berresheim and Jaeschke, 1986). However, recent studies have revived an interest in the formation and fate of atmospheric Criegee intermediates (radical species produced from reactions of ozone with alkenes; Calvert et al, 2000;Criegee, 1975), which to this day have eluded direct measurements in the atmosphere since Cox and Penkett (1971) first suggested their potentially important role.…”
Section: H Berresheim Et Al: Missing So 2 Oxidant In the Coastal Atmentioning
confidence: 99%
“…Martin and Hill (1987) reported an inhibition effect of ionic strength on the rate of the manganese catalyzed oxidation of sulfur; this inhibition effect may be important for the aerosol-phase chemistry due to its high-ionic-strength characteristics. On the other hand, Berresheim and Jaeschke (1986) studied the removal of SO, directly in the presence of different aerosol systems. By using a metal concentration of 55 ng m-3 and RH = 94%, they obtained an SO, removal rate of 2-5% h e ' for Mn(NO,),, 1.5% h-' and 0.09% h -' for MnCl, and MnSO,, respectively, at pH's as low as 1.5.…”
Section: Aerosol-phase Chemistrymentioning
confidence: 99%